2019
DOI: 10.1021/acs.nanolett.9b03330
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Nanoscale Interphases and Morphology of Lithium Metal Electrodes Operating at Low Temperatures

Abstract: While Li-ion batteries are known to fail at temperatures below −20 °C, very little is known regarding the low-temperature behavior of next-generation high-capacity electrode materials. The lithium metal anode is of particular interest for high-energy battery chemistries, but improved understanding of and control over its electrochemical and nanoscale interfacial behavior in diverse conditions is necessary. Here, we investigate lithium deposition/ stripping, morphology evolution, and solid-electrolyte interphas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
174
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(181 citation statements)
references
References 64 publications
7
174
0
Order By: Relevance
“…McDowell's group investigated the morphology evolution and SEI properties during Li plating/stripping process at different temperatures (from −80 to 20 °C) using cryo-TEM coupled with vacuum-transfer XPS (ether-based electrolyte: DOL/DME). [74] The reduced temperatures lead to the smaller Li particles deposited on the current collectors ( Figure 9e). The SEI formed at lower temperature is thinner, chemically and structurally distinct, and less resistive in comparison to the SEI formed at room temperature.…”
Section: Operating Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…McDowell's group investigated the morphology evolution and SEI properties during Li plating/stripping process at different temperatures (from −80 to 20 °C) using cryo-TEM coupled with vacuum-transfer XPS (ether-based electrolyte: DOL/DME). [74] The reduced temperatures lead to the smaller Li particles deposited on the current collectors ( Figure 9e). The SEI formed at lower temperature is thinner, chemically and structurally distinct, and less resistive in comparison to the SEI formed at room temperature.…”
Section: Operating Temperaturementioning
confidence: 99%
“…Reproduced with permission. [74] Copyright 2019, American Chemical Society. Cryo-TEM images and corresponding schematic illustrations of different SEI nanostructure formed at h) 20 °C and i) 60 °C, respectively.…”
Section: Mechanical Strengthmentioning
confidence: 99%
“…[45] Thus, engineering a more favorable SEI could potentially suppress the high surface area growth and dead-lithium formation characteristic to lithium-metal at sub-zero temperatures. [43] McDowell and co-workers recently demonstrated the degree to which cycling in ether versus cyclic carbonate electrolytes affects the subsequent morphology of lithium-metal deposition at low temperatures. [46] Interestingly, they demonstrated that lithium metal deposits cycled in a mixed ether-carbonate formulation tend to be larger on average than those cycled in a pure ether solvent, and subsequently demonstrated better cycling performance at low-temperature conditions.…”
Section: Low-temperature Lithium-metal Batteriesmentioning
confidence: 99%
“…The vast presence of supporting salt at such Reproduced with permission. [43] Copyright 2019, American Chemical Society.…”
Section: Low-temperature Lithium-metal Batteriesmentioning
confidence: 99%
See 1 more Smart Citation